2018
DOI: 10.1016/j.ijgfs.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Steaming and sous-vide: Effects on antioxidant activity, vitamin C, and total phenolic content of Brassica vegetables

Abstract: The present study evaluated the effect of thermal processing on the colour, antioxidant activity, vitamin C content, and total phenols of six Brassica vegetables. The landrace Grelo was the best source of total phenols (162.7 ± 3.5 mg/100g; p<0.05). Cavolo Nero di Toscana, also known as "black cabbage", showed the highest content of vitamin C, calculated as 290.6 mg/100g (p<0.05). The concentration of total antioxidants, phenols, and vitamin C was significantly reduced after both steaming and sous-vide process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 33 publications
(41 reference statements)
3
26
0
Order By: Relevance
“…In addition, the moisture content of the broccoli stems and leaves used for breadmaking was 90.1 ± 1.4 and 82.1% ± 0.6%, respectively. Results compared well in terms of TPC and antioxidant capacity to those recently obtained for the inflorescences and stems of different broccoli varieties (Lafarga, Bobo, Viñas, Zudaire et al, ; Lafarga, Viñas et al, ).…”
Section: Resultssupporting
confidence: 77%
“…In addition, the moisture content of the broccoli stems and leaves used for breadmaking was 90.1 ± 1.4 and 82.1% ± 0.6%, respectively. Results compared well in terms of TPC and antioxidant capacity to those recently obtained for the inflorescences and stems of different broccoli varieties (Lafarga, Bobo, Viñas, Zudaire et al, ; Lafarga, Viñas et al, ).…”
Section: Resultssupporting
confidence: 77%
“…Therefore, we used various in vitro analyses to characterise the antioxidant properties and to comprehensively evaluate the antioxidant quality of radish sprouts. All four antioxidant properties exhibited relatively small losses or even increases under steaming, which was consistent with the results by Lafarga et al (, ), e.g. FRAP activity increased significantly by 14.46% after steaming for 30 s ( P < 0.05), and the activity of FRAP decreased sharply ( P < 0.05) with the increase of time in the late steaming stage (60–300 s), RP was consistent with this, while DPPH and SOD were always in a downward trend.…”
Section: Resultssupporting
confidence: 91%
“…Meanwhile, VC was basically no loss during short‐term steaming. Previous studies have shown that among many cooking methods, steaming is also one of the strongest ways to contribute to vitamin C retention (Francisco et al , ; Lafarga et al , ; Lafarga et al , ). First, steam is based on water vapour as the heat transfer medium, and the raw material and water vapour are basically in a closed environment.…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols, which are classified as secondary plant metabolites, are regarded as an important element of lifestyle diseases prevention due to their antioxidant properties. They have antifungal, anti-inflammatory and antiviral properties, and they decrease the risk of tumours and osteoporosis [ 46 ]. The negative influence of thermal processing on polyphenol content in plant-derived materials has been described by numerous authors, who explain the phenomenon by the Maillard reaction [ 47 ], polymerisation [ 48 ], or oxidation and condensation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%